KONSEP DIRI PENGHAYAT KEPERCAYAAN KEPADA TUHAN YANG MAHAESA DI YAYASAN CENDEKIAWAN KAMPUNG INDONESIA - Atih Ardiansyah (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2022)
This research aims to find out the self-concept of Penghayat Kepercayaan who became a Genius Kampung at the Cendekiawan Kampung Indonesia Foundation with a focus on self-esteem, self-role and self-identity. The method used is a qualitative method with a case study approach. Based on data obtained through participatory observation, review documents, and in-depth interviews, it was found that, first, the Penghayat Kepercayaan at the Cendekiawan Kampung Indonesia Foundation interpreted and had positive self-esteem, he felt proud as a Genius Kampung as well as a Penghayat Kepercayaan. Second, Penghayat Kepercayaan at the Cendekiawan Kampung Indonesia Foundation interprets its role as a public relation for the Genius Kampung community as well as for the Penghayat Kepercayaan community. Third, Penghayat Kepercayaan at Cendekiawan Kampung Indonesia Foundation presents its identity as an open-minded and feels no different from others.Keywords: intercultural communication, self-concept, Penghayat Kepercayaan, Cendekiawan Kampung